The Substitution of Purslane Weed (Portulaca oleracea L.) Flour and Glucomannan Powder on Organoleptic and Proximate Test of Instant Noodles - Wati, Dini Prastyo; Fajrina, Meinira Dinar; Putra, Sahasika Sean; Suryani, Titik (Journal of Agri-Food Science and Technology, 2024)
Instant noodles are a food product that the public highly favors because of their diverse taste, easy presentation, and economical price. Instant noodles cannot be considered whole food because they do not meet the needs of balanced nutrition for the body. Purslane flour (Portulaca oleracea L.) contains macronutrients and micronutrients in the form of carbohydrates, protein, dopamine, potassium salts, tannins, saponins, vitamin A (β-carotene), Vitamin B, Vitamin C, nicotinic acid and natural antioxidants related to fatty acids omega 3 by 44.29%. This study contributed to compare the effectiveness of the substitution of Purslane flour and glucomannan powder on organoleptic test instant noodles. This study was an experiment with a completely randomized design of two-factorial with six treatments including the formulation of purslane flour 25%, 30%, and 35%, while glucomannan formulation of 5%, 10%, 15% with two temperature treatments, 50 °C, and 60 °C. We conducted an organoleptic test with statistical analysis t-test and descriptive. The substitution of purslane flour and glucomannan in instant noodles gave the best organoleptic characteristics in the K2S2 treatment (the formulation of 60% wheat flour, 30% purslane flour, and 10% glucomannan at a drying temperature of 60 °C) with proximate analysis content of 12.26% moisture, 5.53% ash, 5.13% fat, 13.91% protein, and 63.14% carbohydrates.